Effect of plant types on grain yield and lodging resistance in pea (Pisum sativum L.) - Singh, A.K.; Srivastava, C.P. (The Indian Journal of Genetics and Plant Breeding, 2016)
In the present experiment 56 diverse pea genotypes were chosen belonging to seven different plant type groups and observations were made on eight traits related to yield and lodging. Normal foliage with reduced stipule plant type (stst genotype) found to be shortest (in terms of days to flowering and days to maturity) while, semi-leafless plant type had the highest 100-seed weight as compared to the normal plant types (LeLe AfAfTlTl StSt). On the other hand, the pleiofila with reduced stipule foliage type (afaf tltl stst) had smallest 100-seed whereas, seed yield per plant was highest in case of semi-leaf plant types in both tall and dwarf groups. Similarly, Pleiofila with normal and reduced stipule plant types in both tall and dwarf groups were found to be more lodging susceptible than the normal.The dwarf/semi-dwarf genotypes combined with semi-leafless peas appear to be the most ideal plant type that would provide better tolerance to lodging and yields high.